2013
DOI: 10.1186/1471-2458-13-1008
|View full text |Cite
|
Sign up to set email alerts
|

Thailand’s HIV/AIDS program after weaning-off the global fund’s support

Abstract: Background: Though 85% of financing HIV/AIDS program was domestic resources, Global Fund (GF) programs played a significant role in prevention interventions and treatment for non-Thai Key Affected Populations (KAP) and migrants. As upper-middle income country, Thailand is not eligible for GF support. This study identified the remaining challenges and funding for prevention interventions for Thai and non-Thai KAP and migrants if GF supports were to curtail. Methods:Qualitative method was applied including docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…A recent study by Martin in 2007 suggested over 1.3 million migrants in Thailand were unregistered, about triple the number of registered migrants in that year 83. As a result, the responsibility of taking care of this hard-to-reach popula tion who were often engaged with other populations at risk, eg, men who have sex with men and people who inject drugs, were mostly shouldered by nongovernmental organizations (NGOs) in the country 84. Those NGOs thereby mobilized resources from Global Fund (GF) to support their activities for non-Thai key affected populations and migrants.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Martin in 2007 suggested over 1.3 million migrants in Thailand were unregistered, about triple the number of registered migrants in that year 83. As a result, the responsibility of taking care of this hard-to-reach popula tion who were often engaged with other populations at risk, eg, men who have sex with men and people who inject drugs, were mostly shouldered by nongovernmental organizations (NGOs) in the country 84. Those NGOs thereby mobilized resources from Global Fund (GF) to support their activities for non-Thai key affected populations and migrants.…”
Section: Discussionmentioning
confidence: 99%
“…A majority share of total AIDS spending, 50% in 2015, was used for ART [7] as a result of rapid expansion of ART coverage. The international funding was largely for HIV prevention [1], accounted for 29-42% of total international funding during 2008-2013. However, international partners spending had shifted to Systems Strengthening & Programme Coordination which increased from 32% in 2014 to 41% in 2015.…”
Section: Journal Of Clinical and Cellular Immunologymentioning
confidence: 99%
“…Such good governance and accountability should be applied and replaced the current integrated model where MOPH plays two roles: funding and implementation agency where there is limited accountability [1]. The Thai UC Scheme where National Health Security Office is the financing agent which purchases services from the public and private health care providers had demonstrated better accountability to the citizens [10].…”
Section: Program Governancementioning
confidence: 99%
See 1 more Smart Citation
“…The Thai 2014 national PMTCT guidelines are in accordance with WHO recommendations for Prongs 3 and 4, and these overlap in interventions aimed at them. Prong 3 includes testing pregnant women for HIV, providing HIV-infected pregnant women with ART as soon funding from multiple domestic sources has been proposed [56]. More interventions are required to encourage mothers who are HIV-positive to access post-partum care services because 40% do not.…”
Section: The Future Challenges and Evolution Of Pmtct In Thailandmentioning
confidence: 99%